Hematological, inflammatory, and novel biomarkers assessment as an eminent strategy for clinical management of COVID-19 - Sanaz Rezaeian; Fatemeh Razmjooei; Masoome Pourmokhtari; Amir Abdoli; Mirza Ali Mofazzal Jahromi; Kambiz Bagheri (Heliyon, 2023)
Background: Different biomarkers have been suggested as novel biomarkers of coronavirus disease 2019 (COVID-19) theragnosis. With the aim of having a better clinical management of COVID-19, we decided to determine the relationship between hematological, inflammatory, and novel biomarkers with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) immunoglobulin (Ig)M and IgG antibodies. Methods: Blood samples from 127 confirmed COVID-19 patients aged 11–84 years old were collected and tested for SARS-CoV-2 IgM and IgG antibodies alongside with hematological, inflammatory, and novel biomarkers. The Spearman correlation test was utilized to analyze the correlation between these biomarkers with SARS-CoV-2 IgM and IgG antibodies. Results: The SARS-CoV-2 IgM antibody significantly correlated with erythrocyte sedimentation rate (ESR) (r = 0.329, p = 0.000), C-reactive protein (CRP) (r = 0.459, p = 0.000), interleukin (IL)-6 (r = 0.345, p = 0.000), IL-8 (r = 0.263, p = 0.003), neutrophil to lymphocyte ratio (NLR) (r = 0.182, p = 0.040), derived NLR (dNLR) (r = 0.197, p = 0.026), neutrophil to monocyte ratio (NMR) (r = 0.184, p = 0.038), and CRP to lymphocyte ratio (CLR) (r = 0.495, p = 0.000). Also, we find significant correlation between SARS-CoV-2 IgG antibody with hemoglobin (Hb) (r = −0.257, p = 0.004), hematocrit (Hct) (r = −0.227, p = 0.010), mean corpuscular Hb concentration (MCHC) (r = −0.212, p = 0.017), lymphocyte count (r = −0.211, p = 0.017), platelet count (r = 0.179, p = 0.044), ESR (r = 0.461, p = 0.000), CRP (r = 0.344, p = 0.000), IL-6 (r = 0.178, p = 0.046), IL-8 (r = 0.237, p = 0.007), platelet to lymphocyte ratio (PLR) (r = 0.295, p = 0.001), and CLR (r = 0.376, p = 0.000). Conclusion: Hematological biomarkers (Hb, Hct, MCHC, lymphocyte count, and platelet count), inflammatory biomarkers (ESR, CRP, IL-6, and IL-8), and novel biomarkers (dNLR, NLR, NMR, PLR, and CLR) are valuable indicators for clinical management of COVID-19.